Cyber Espionage in National and Global Perspective: How Indonesia Deal with this issue? - Dewi, Maharani Chandra (International Law Discourse in Southeast Asia, 2022)
Cyber Crime is the most frightening crime in today's technological developments. Attacks that do not know the target and time for a particular purpose. The privacy of a person or institution can be threatened by cyber crime. Mobile technology and supported by adequate communication network facilities turn a positive image into a dilemma. Someone should in dealing with it keep thinking positive. Increasing self-awareness and acting ethically will not result in something fatal. Any excessive action can backfire. Increasing knowledge in the use of technology is very necessary. Mobilization that is too widespread makes it easier to access information. Cyber crime will not happen if we do not do strange and disturbing things.